Analisis Perlakuan Akuntansi Aset Tetap dan Penyajiannya pada Laporan Keuangan PT Tanjung Migas (Spbu 14.203.159) Kabupaten Deli Serdang Sumatera Utara - Sastra Karo-Karo; Asriyati Asriyati; Sudarsono Sudarsono; Samuel Sinurat (Jurnal Riset Ekonomi dan Akuntansi, 2023)
This research discusses fixed asset accounting at PT Tanjung Migas (SPBU 14.203.159). The purpose of this research is to determine the compliance of fixed asset accounting applied by PT Tanjung Migas (SPBU 14.203.159) in Deli Serdang Regency with the Financial Accounting Standards for Entities without Public Accountability No. 15 of 2009. The data used in this research are primary data and secondary data. The data collection techniques used are interviews and documentation, and the data processing technique in this research is descriptive analysis method. The results of this research indicate that the implementation of fixed asset accounting at PT Tanjung Migas (SPBU 14.203.159) in Deli Serdang Regency is in accordance with the Financial Accounting Standards for Entities without Public Accountability No. 15 of 2009.